Epilepsy in the British Steel Corporation: an evaluation of sickness, accident, and work records. Issue 2 (May 1982) - Dasgupta, A K; Saunders, M; Dick, D J
Abstract : Information relating to sickness, accident, and work records in 45 people with epilepsy employed in the British Steel Corporation was obtained and compared with 38 matched control subjects. Fewer people with epilepsy were prepared to do shift work compared with controls, and prolonged absence from work due to sickness was more frequent in the epileptic group. There was no difference between the two groups in four out of five factors relating to job performance. Those in the epileptic group who had an associated personality disorder had significantly poorer job performance ratings.